Implementación de un sistema de contabilidad de costos abc, en la empresa florícola Rosely Flowers, ubicada en la parroquía Aláquez, cantón Latacunga, provincia de Cotopaxi, en el periodo 01 de agosto al 31 de diciembre del 2013 - Cunuhay Chusin, Norma Llaneth (2015)
This research places the true cost of production rose stem, taking into account the activities in each of the processes. The research was used to develop the thesis was descriptive, not experimental methodology, using inductive and deductive methods, analytical - synthetic and statistical methods, the technique used for data collection were directed interview the Managing Owner Floriculture, in order to meet the organizational and administrative role of the company, the survey was applied to administrative and scientific observation applied to the production stages of the rose, which revealed the production management which facilitates decision making. The research process determined that in the mentioned flower industry ignorance of what is an waste and cost was a serious problem affecting the proper allocation of costs and therefore prevented identify actual costs in each of the activities production stages. Based on this research work it was possible to conclude that the implementation of a cost accounting system ABC, yielding the unit cost of the stem and used for taking decisions.